Tingkat Kepekaan Bilangan (Number Sense) Siswa Sekolah Dasar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Number sense is a person's perspective on a number and its calculations. A person with a good sense of numbers can use various methods and strategies to solve complex problems. This research is motivated by the lack of number sense, this is because the methods used in the learning process still use traditional mathematics teaching. This research is an ex post facto research where data is reviewed with a qualitative approach and presented descriptively. The results of the study show that the level of number sense in elementary school students is able to understand the basic meaning of numbers and operations, use the right benchmarks, assess the fairness of the results, but have not been able to realize the relative and absolute magnitude of a number.